HUBUNGAN ANTARA KOORDINASI MATA TANGAN, POWER OTOT LENGAN DAN KEKUATAN OTOT PERUT DENGAN KEMAMPUAN PUKULAN SMASH DALAM PERMAINAN BULUTANGKIS - Ghon Lisdiantoro (Universitas PGRI Madiun, 2016)
This study has a purpose to determine the relationship between each variable. This study used descriptive correlational study. The study population was students of IKIP PGRI MADIUN in total 60 students. The research sample was 30 male students with techniques purposive sampling. This research resulted in the following conclusions: (1) there is a significant correlation between hand-eye coordination with the ability to smash, the correlation coefficient of 0.550. With N = 30, 5% value rtabel 0463. Turns rhitung = 0.550> 5% rtabel 0463. (2) there is a significant correlation between muscle power arm with the ability to smash, the correlation coefficient of 0.651. With N = 30, 5% value rtabel 0463. Turns r hitung = 0651> r tabel 5% 0463 (3) there is a significant correlation between the strength of the abdominal muscles with the ability to smash, the correlation coefficient of 0.549. With N = 30, 5% value r tabel 0463. Turns r hitung = 0549> 5% r tabel 0463. (4) there is a significant correlation between hand-eye coordination, power arm muscles and abdominal muscle strength with the ability to smash, Retrieved of 12,581 correlation coefficient, with F table db = 3 opponents 26 with a significance level of 5% = 4.64 turns F regresi price = 12.581 > prices F tabel 5% = 4.64.